2009
DOI: 10.1002/ptr.2917
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic effect of aqueous extract of seabuckthorn (Hippophae rhamnoides L.) seed residues in streptozotocin‐induced diabetic rats

Abstract: An extract of seabuckthorn (Hippophae rhamnoides L.) seed residues has been shown to possess hypoglycemic and hypolipidemic properties in normal mice. The present study investigated the effects of an aqueous extract of seabuckthorn seed residues (ASSR) on serum glucose, lipid profiles and antioxidant parameters in streptozotocin-induced diabetic rats. Male Sprague-Dawley rats were divided into four groups: a normal control group; diabetic control group; diabetic groups supplemented with 5 mg/kg body weight gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 19 publications
5
33
0
Order By: Relevance
“…In this investigation, the concentrations of MDA and NO were decreased after treating with TFE or TTE, indicating the inactivation of LPO reactions and the decreased free radical generation. Furthermore, in our study, the activities of SOD (a scavenger of free radicals) and GSH (a major endogenous antioxidant) decreased in diabetes group as reported earlier (Gokce and Haznedaroglu, 2008;Zhang et al, 2010) which could be due to inactivation caused by STZ-generated ROS. Treatment of diabetes with the TTE or TFE had reversed the activities of these enzymatic antioxidants, which might be due to decreased oxidative stress as evidenced by decreased LPO.…”
Section: Discussionsupporting
confidence: 51%
“…In this investigation, the concentrations of MDA and NO were decreased after treating with TFE or TTE, indicating the inactivation of LPO reactions and the decreased free radical generation. Furthermore, in our study, the activities of SOD (a scavenger of free radicals) and GSH (a major endogenous antioxidant) decreased in diabetes group as reported earlier (Gokce and Haznedaroglu, 2008;Zhang et al, 2010) which could be due to inactivation caused by STZ-generated ROS. Treatment of diabetes with the TTE or TFE had reversed the activities of these enzymatic antioxidants, which might be due to decreased oxidative stress as evidenced by decreased LPO.…”
Section: Discussionsupporting
confidence: 51%
“…In a recent study antidiabetic effect of an aqueous extract from SBT seed residues has been demonstrated [12].…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is reported to be well tolerated and without any untoward reaction or side effects in toxicological studies [11]. It is interesting to note that SBT has recently been reported to possess hypoglycemic activity [12]. In view of all the above reports, we chose to evaluate SBT for possible beneficial effect on STZ-induced hyperglycemia and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…The studies concerning the effects of sea buckthorn (SB) and/or bilberry (BB) on metabolic diseases are presented below. In animal studies SB has shown positive effects on cardiovascular health (Yang et al, 2007;Pang et al, 2008;Koyama et al, 2009) and diabetes (Zhang et al, 2010). Also, positive effects of anthocyanin extract from blueberry on vascular health have been proposed based on in vitro (Bell and Gochenaur, 2006) and animal trials (Cohen-Boulakia et al, 2000).…”
Section: Introductionmentioning
confidence: 99%